Ion‐Selective Organic Electrochemical Transistors. (23rd May 2014) - Sessolo, Michele; Rivnay, Jonathan; Bandiello, Enrico; Malliaras, George G.; Bolink, Henk J.
<x xml:space="preserve">Abstract</x> Ion‐selective organic electrochemical transistors with sensitivity to potassium approaching 50 μA dec−1 are demonstrated. The remarkable sensitivity arises from the use of high transconductance devices, where the conducting polymer is in direct contact with a reference gel electrolyte and integrated with an ion‐selective membrane. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>